Song of the Wayfarer: Auvergne According to François Cassingena-Trévedy - Eric Bordessoule; Michel Lompech (Revue de Géographie Alpine)
There are different approaches to writing travel narratives and literature about mountain wayfaring. This article studies the journey of a contemporary writer in the highlands. By providing a historical context for the space crossed and by confronting the expressed emotions brought on by the landscape which led to the marginalization of the Cézallier massif, the study shows how one can elaborate on the experiences felt in a certain location and give a sense of place and represent the countryside in a sensitive way.